TATA KELOLA PASAR DESA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA (Study Pemerintah Desa): Study Pemerintah Desa - Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Ayu Windarky; Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Jenny Yudha Utama; Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Santosa (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2021)
The market is a mechanism that brings together buyers (consumers with sellers) and producers so that both can interact to form an agreement. The role of the Village Government in structuring traditional markets in Dlanggu Village, Dlanggu District, Mojokerto Regency is very important because the village market is a meeting place for sellers and buyers to conduct transactions or buying and selling goods and services, so that village markets can be crowded and develop, village market arrangements are needed. With governance by the village, it is hoped that later it will improve the welfare of the people in the village.This study uses a qualitative method, the data collection method used is using interviews, observations or observations with references to previous research and journal references to analyze research results. This research is descriptive analysisThis research is analyzed with George's Organizational Management Theory. R. Terry so that later he can get results on how the impact on the welfare of the community in Dlanggu Village, opens up job opportunities for the Dlanggu village community itself, and from that the income that the village gets from Tanjungsari Market is very profitable for the village with income from Tanjungsari Market can be used to build public facility services such as village health centers and others